The Investigation on Electrical Characteristic of Saline Solution - Chaisiri, Punyavee; Yutthagowith, Peerawut (My University, 2019)
This paper presents the investigation of electrical characteristic of saline solution in the term of electrical resistivity and relative permittivity in the frequency range from 100 Hz to 100 MHz. The electrical resistivity and relative permittivity are calculated from resistance and capacitance of saline solution. The experimental results provide the technical data of the insulating liquid which is very useful for liquid insulator design applied for a part of high volt component.
Keywords: Electrical resistivity; High Voltage Measurement; Relative permittivity; Saline solution; Voltage Divider